Providing community based services to the rural elderly (Sage focus edition, 1994)
Researchers and practitioners, pairing to co-author most chapters, present detailed information on a wide range of community-based services that are needed by and available to elders living in rural areas. These contributors explore how such services can be developed given the realities of rural settings, resources, and populations. They identify the barriers to development and operation, and offer possible solutions